Structure and Dynamics of Humpback Whales Competitive Groups in Ecuador - Fernando Félix; Johana Novillo (Animal Behavior and Cognition, 2015)
We assessed the social structure and behavior of humpback whale (Megaptera novaeangliae) competitive groups off Ecuador between July and August 2010. During this time we followed 185 whales in 22 competitive groups for 41.45 hr. The average group size was 8.4 animals (SD = 2.85). The average sighting time was 113.05 min/group (SD = 47.1). We used photographs of dorsal fins and video to record interactions and estimate an association index (AI) between each pair of whales within the groups. Sightings were divided into periods, which were defined by changes in group membership. On average, group composition changed every 30.2 min, which confirms that the structure of competitive groups is highly dynamic. Interactions between escorts characterized by low level of aggression. At least 60% of escorts joined or left together the group in small subunits between two and five animals, suggesting some type of cooperative association. Although singletons, as well as pairs or trios were able to join competitive groups at any moment, escorts that joined together were able to stay longer with the group and displace dominant escorts. Genetic analysis showed that in three occasions more than one female was present within a competitive group, suggesting either males are herding females or large competitive groups are formed by subunits. Males and females performed similar surface displays. We propose that competition and cooperation are interrelated in humpback whales’ competitive groups and that male cooperation would be an adaptive strategy either to displace dominant escorts or to fend off challengers.